Competing for Talent: Firms, Managers, and Social Networks. (22nd February 2021) - Hacamo, Isaac; Kleiner, Kristoph
Abstract: Do social networks help firms recruit talented managers? In our setting, firms are randomly connected to prospective young managers through former employees. Under a discrete choice model, we find networks increase the likelihood firms hire high-ability managers, while having no effect on the hiring rate of low-ability managers. Effects are greatest for nonlocal firms, strong ties, and peers living in the same neighborhood. Survey evidence suggests social networks promote recruitment by providing information about firm fundamentals to potential applicants. Our results help rationalize why the majority of managers hold prior connections to the firm.